2018
DOI: 10.3382/ps/pey276
|View full text |Cite
|
Sign up to set email alerts
|

Influence of a specific amino acid pattern in the diet on the course of an experimental Campylobacter jejuni infection in broilers

Abstract: Campylobacter jejuni (C. jejuni) is one of the most important zoonotic pathogens worldwide. In Europe, the majority of the cases are caused by consuming contaminated poultry meat. The objective of the present study was to investigate potential effects of different crude protein levels in complete diets for broilers on infection dynamics of C. jejuni after experimental infection. In total, 300 commercial broilers line Ross 308 were divided into 4 different groups, including 5 replications of 15 chickens each. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 43 publications
(55 reference statements)
0
16
0
Order By: Relevance
“…Varying amino-acid concentrations in the diet of broiler chickens preferentially utilised by C. jejuni , such as aspartate, glutamate, proline and serine are able to influence the spread and the shedding of C . jejuni (Visscher et al, 2018). It can be hypothesised that an environment favouring C. jejuni metabolism should also favour growing conditions of Parasutterella , as their metabolism relies on similar amino acids.…”
Section: Discussionmentioning
confidence: 99%
“…Varying amino-acid concentrations in the diet of broiler chickens preferentially utilised by C. jejuni , such as aspartate, glutamate, proline and serine are able to influence the spread and the shedding of C . jejuni (Visscher et al, 2018). It can be hypothesised that an environment favouring C. jejuni metabolism should also favour growing conditions of Parasutterella , as their metabolism relies on similar amino acids.…”
Section: Discussionmentioning
confidence: 99%
“…Supplementing broiler diets with protein sources other than soybean may provide a different amino acid pattern in the diet. Distinct dietary amino acid patterns can potentially reduce the prevalence of Campylobacter infection in chickens (Visscher et al, 2017(Visscher et al, , 2018. Additionally, several studies indicated that soybean meal-based diets increase crude mucin excretion in the intestinal tract of birds (Adedokun, 2007;Horn et al, 2009;Visscher et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Distinct dietary amino acid patterns can potentially reduce the prevalence of Campylobacter infection in chickens (Visscher et al, 2017(Visscher et al, , 2018. Additionally, several studies indicated that soybean meal-based diets increase crude mucin excretion in the intestinal tract of birds (Adedokun, 2007;Horn et al, 2009;Visscher et al, 2018). The presence of mucin appears to be essential for the survival and growth of C. jejuni in the poultry gut (Van Deun et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…This isolate had been identified as C. jejuni both culturally and mass-spectrometrically (MALDI-TOF MS; AniCon Labor GmbH, Höltinghausen, Germany). Preparation of the conserved strain for experimental infection was done as previously described ( 33 ). The infection strain was used in its stationary growth phase (24–48 h) for preparing the inoculum.…”
Section: Methodsmentioning
confidence: 99%
“…The content of total mucin was determined in birds‘ pooled excreta. Quantifying the water-soluble and ethanol-precipitable fraction of excreta was carried out in accordance with modified methods ( 9 , 35 ) as described by Visscher et al ( 33 ).…”
Section: Methodsmentioning
confidence: 99%